PERKEMBANGAN SMART CITY TANGERANG SELATAN TAHUN 2016-2021 - Irfan Aufar Azmi; Achmad Djunaedi (Jurnal Perencanaan dan Pengembangan Kebijakan, 2022)
Uneven development causes the level of urbanization to be higher, which causes urban problems in both physical and non-physical forms. Based on this, the City of South Tangerang is increasing the development of the city into a Smart City. This study examines the stages of development of South Tangerang City into a smart city. This research is a qualitative descriptive study, with data collection techniques using interview techniques, in-depth observation, and documentation studies. Research theory using city management, and smart city. The results of this study are the stages of South Tangerang City towards Smart City in 2016-2021 is a development that can be said to be short, consisting of three stages. The first stage 2016-2017 is the preparation stage in the form of internal strengthening. The second stage 2017-2018 is the planning stage in the form of policy formulation and implementation guidelines for Smart City. And the third stage (2018-2021) which is the stage of implementing the plan in the form of achieving targets and indicators that are continuously monitored and evaluated. Based on the results obtained, it can be concluded that the stages planned by the South Tangerang government in building a smart city can fulfill the smart city vision.